2019
DOI: 10.1103/physrevd.99.116025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anomalous magnetic moment of quarks on the phase structure and mesonic properties in the NJL model

Abstract: Employing a field dependent three-momentum cut-off regularization technique, we study the phase structure and mesonic masses using the 2-flavour Nambu-Jona Lasinio model at finite temperature and density in presence of arbitrary external magnetic field. This approach is then applied to incorporate the effects of the anomalous magnetic moment(AMM) of quarks on constituent quark mass and thermodynamic observables as a function of temperature/baryonic density. The critical temperature for transition from chiral s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 98 publications
9
86
2
Order By: Relevance
“…9, we have shown the variation of m π as a function of temperature at two different values of an external magnetic field. At lower values of temperature, the mass of pions are almost independent of T. At some particular temperature, m π suffers a sudden jump (discontinuity) corresponding to Mott transition [41,42,[53][54][55]. The jump structure is in qualitative agreement with most of the studies.…”
Section: Numerical Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…9, we have shown the variation of m π as a function of temperature at two different values of an external magnetic field. At lower values of temperature, the mass of pions are almost independent of T. At some particular temperature, m π suffers a sudden jump (discontinuity) corresponding to Mott transition [41,42,[53][54][55]. The jump structure is in qualitative agreement with most of the studies.…”
Section: Numerical Resultssupporting
confidence: 85%
“…However, there exist differences in the quantitative nature of the jump structure. For example, the amount of discontinuity obtained here is smaller in comparison to [42] which itself is different from [53] as well as [41]. One should observe that different parameter sets have been chosen in all these cases along with different regularization procedures.…”
Section: Numerical Resultsmentioning
confidence: 84%
“…Another approach to obtain results in both NJL and PNJL models (with constant coupling) consistent with the lattice calculation is the inclusion of anomalous magnetic moment (AMM) of the quarks. Recently, there has been a lot of activity in this direction involving both NJL and PNJL models to study the phase structure as well as the mesonic excititations ( and ) [73][74][75][76][77]. The values of the AMM of the quarks can be taken as constant [73,75,76] or temperature and magnetic field dependent [77]; in either case the values must reproduce the vacuum values of the AMM of the proton and neutron.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a lot of activity in this direction involving both NJL and PNJL models to study the phase structure as well as the mesonic excititations ( and ) [73][74][75][76][77]. The values of the AMM of the quarks can be taken as constant [73,75,76] or temperature and magnetic field dependent [77]; in either case the values must reproduce the vacuum values of the AMM of the proton and neutron. With the inclusion of the AMM of the quarks both in the NJL and PNJL models with constant coupling, it has been found that the critical temperature decreases with the magnetic field leading to inverse magnetic catalysis (IMC) [73,75,76].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anomalous magnetic moment of the quark [1,2,3,4,5,6,7,8,9] attracted much interest in investigating QCD matter under strong magnetic field created through noncentral heavy ion collisions [10,11]. It has been known that the magnetic field catalyzes the chiral condensate of spin-0 quark-antiquark pair which carries net magnetic moment and triggers a dynamical anomalous magnetic moment (AMM) of quarks [12,13,34].…”
Section: Introductionmentioning
confidence: 99%